Numerical Modelling of Soft Soil Improvement Using Expanded Polystyrene Geofoam for Road Embankment - yusof, Mohd Fairus (Journal of Sustainable Underground Exploration, 2022)
Soft soil brings abundant engineering issues due to low bearing capacity and shear strength. A comprehensive study of soft ground needs to be reviewed and identified before construction can start. Various techniques can be used to improve the soil. However, this study focuses on using material, namely expanded polystyrene. The geotextile is embedded with expanded polystyrene to strengthen the soil condition. This study adopted the soil parameters from East Coast Expressway 2. There are two models in this study, which are earth embankment and EPS embankment. The settlement of the earth embankment is compared with the EPS embankment after construction. The Mohr-Coulomb parameters are used to model soft soil and embankments, while the linear elastic parameters were adopted to model the EPS and geotextile. This study produced two embankment models, the conventional embankment models with and without surcharge. The second model is an EPS embankment with various densities (22 kg/m3, 29 kg/m3, and 39 kg/m3). The settlement is recorded for ten years after the embankment construction was completed. The difference settlement value for the conventional model is 28 mm. The settlement value for EPS 22 is 3.18 mm, EPS 29 is 2.06 mm, and EPS 39 is 1.51 mm. For the geotextile embedded with EPS settlement value, EPS 22 is 3.17 mm, EPS 29 is 2.04 mm, and EPS 39 is 1.49 mm. Since EPS uses three different densities, from the prediction of PLAXIS 2D, the higher density gives the lower value of the settlement. However, when the geotextile is embedded with EPS, there is no significant difference when using geotextile. In conclusion, the model with a surcharge gives a lower settlement than the model without a surcharge. But the expanded polystyrene block is the best model to reduce the settlement compared with the conventional model with a surcharge. Different density of EPS gives different settlement value, and EPS 39 gives the lowest settlement value. In terms of the geotextile embedded with EPS, it does not give a significant settlement.